Mosque-based anti-corruption village: Community empowerment program in Prenggan, Kemantren Kotagede Yogyakarta - Suyadi Suyadi; Waharjani Waharjani; Sumaryati Sumaryati; Trisna Sukmayadi; Saedah Binti Siraj (Community Empowerment, 2022)
Village Prenggan, Kemantren Kotagede Yogyakarta has been piloting an anti-corruption village by the Komisi Pemberantasan Korupsi (KPK) since 2013. However, until now (2022) the village has not succeeded in becoming an anti-corruption village. In fact, the KPK prefers Kelurahan Panggungharjo, Bantul Regency as the first anti-corruption village in Yogyakarta. This is because the anti-corruption village programs in Prenggan have not been carried out thoroughly. This article is the result of a community empowerment program in Prenggan village towards an anti-corruption village. The target partner groups for this community service are the Prenggan Mubaligh Association (Paguyuban Mubaligh Prenggan) and the TK ABA Komplek Masjid Perak Yogyakarta. The methods used are training, counseling and anti-corruption assistance. The results of this community service show that: 1) The Prenggan Mubaligh Association has succeeded in developing anti-corruption propaganda gendhings. Every preacher who preaches always carries a message of anti-corruption values ​​with a touch of art; 2) The TK ABA Komplek Masjid Perak, which originally had an anti-corruption literacy reading, has now succeeded in completing it with anti-corruption exercises. Anti-corruption literacy is a ratio exercise, while anti-corruption gymnastics is a sport. As for the values ​​of Islam and Aisyiyahan are the feelings or the heart. Thus, the TK ABA Komplek Masjid Perak combines ratio training through anti-corruption literacy, sports through anti-corruption gymnastics, and heart exercises through Islamic values. In fact, this school became the prototype of the first anti-corruption school at the early childhood level in Indonesia. Thus, a mosque-based anti-corruption village that is more bottom-up in nature can be a complement to the anti-corruption village formed by the KPK which is more top-down.